What can not forget - Morales Camacho, María (2024)
Thus, this current issue 97.1 of our International Relations Journal gathers different articles fosued on diverse dimensions of the international scenario. This issue includes topics linked to economy and international trade, international cooperation and geopolitics where conflicts and international humanitarian crisis can be part of this reality that must be studied from a broad perspective.